Once you think you're wrong, you must be right: new versions of the preface paradox. - Williams, John N. (Synthese)
I argue that there are living and everyday case in which rationality requires you, as a non-idealized human thinker, to have inconsistent beliefs while recognizing the inconsistency. I defend my argument against classical and insightful objections by Doris Olin, as well as others. I consider three versions of the preface paradox as candidate cases, including Makinson's original version. None is free from objection. However, there is a fourth version, Modesty, that supposes that you believe that at least one of your beliefs (excluding this) is false. I argue that this version escapes all the objections that could trouble the other versions, including the objection that given certain closure principles for justified belief, justified inconsistent beliefs saddle you with a pair of justified beliefs that are in explicit contradiction (their contents being syntactic negations). I also argue more tentatively for the same verdict for Modesty*, a version that supposes that you believe that at least one of your beliefs (including this) is false. In that case, your belief guarantees that its content is true, in which case your beliefs are inconsistent, because at least one of them must be false. Once you think you're wrong, you must be right! Crucial to my argument is a distinction between explicitly contradictory beliefs and three forms of inconsistency in belief. In the first of these, you believe contingent propositions each of which is logically independent of the others, yet you also believe the syntactic negation of their conjunction. In the second, your beliefs are inconsistent because of the rigid designation of demonstratives such as 'this' embedded in their contents. In the third, as in Modesty and Modesty* your beliefs are inconsistent because of self-reference.